Design and kinematics analysis of the executing device of heavy-duty casting robot. (7th January 2020) - Wang, Chengjun; Xu, Chengke; Li, Long; Hu, Haixia; Guo, Yongcun
Aim to the problems of low load and precision of the serial manipulator used in casting operation. Casting execution equipment based on 2UPR-2RPU mechanism was designed. A prototype of heavy-duty casting robot has been proposed and developed. Based on the theory of robot topology, the mechanism constraint relation of the casting execution equipment was analyzed, and it is concluded that the casting actuator has three degrees of freedom. Both the inverse position equation of the casting execution equipment and axial velocity equation of branch chain were established. In this article, kinematics simulation of the casting execution equipment based on ADAMS software was presented, and its kinematics characteristics of each parallel branch chain were analyzed. The validity of this kinematics model of casting actuator was verified. Based on the working space analysis method for parallel mechanism, the working space range of casting execution equipment was simulated by the MATLAB software. This research provides a reference for expanding the application of hybrid structural robot in casting field and developing casting heavy-duty casting robotic products.